Changing networks and alliances in a transnational context: Salvadoran and Guatemalan immigrants in southern California - Chinchilla, Norma Stoltz (Social justice, 1999)
Part of a special issue on collective identities, social problems, and movements. The writers discuss the changing networks and alliances of Salvadoran and Guatemalan immigrants in Southern California in a transnational context. They examine this by considering the relationship between globalization of capital, international migration, and transnationalism, acknowledging the historical and contemporary dimensions. They conclude that transnationalism is affected by the economic and social context and that new transnational practices emerge as this context changes; that transnational practices of Salvadoran and Guatemalan migrants have led to strengthened networks with their communities of origin that have, in turn, transformed these communities and even national economies; that nonmigrants have an important role in transnational migrant practices; and that transnationalism has ambiguous implications for power relations, stratification systems, and counter-hegemonic practices.